A Roadmap for Genome-Based Phage Taxonomy - Turner, Dann; Kropinski, Andrew M.; Adriaenssens, Evelien M. (Viruses, 2021)
Bacteriophage (phage) taxonomy has been in flux since its inception over four decades ago. Genome sequencing has put pressure on the classification system and recent years have seen significant changes to phage taxonomy. Here, we reflect on the state of phage taxonomy and provide a roadmap for the future, including the abolition of the order Caudovirales and the families Myoviridae, Podoviridae, and Siphoviridae. Furthermore, we specify guidelines for the demarcation of species, genus, subfamily and family-level ranks of tailed phage taxonomy.